Ultrastrong silk fabric ionogel-sensor for strain/ temperature/ tactile multi-mode sensing - Shu Wang; Jiangling Ning; Jianyu Pu; Changjie Wei; Yuping Yuan; Songqi Yao; Yuantao Zhang; Ziwen Jing; Chenxing Xiang; Xinglong Gong; Zhi Li; Ning Hu (Nano Materials Science, 2025)
Ionogels have demonstrated substantial applications in smart wearable systems, soft robotics, and biomedical engineering due to the exceptional ionic conductivity and optical transparency. However, achieving ionogels with desirable mechanical properties, environmental stability, and multi-mode sensing remains challenging. Here, we propose a simple strategy for the fabrication of multifunctional silk fabric-based ionogels (BSFIGs). The resulting fabric ionogels exhibits superior mechanical properties, with high tensile strength (11.3 ​MPa) and work of fracture (2.53 ​MJ/m3). And its work of fracture still has 1.42 ​MJ/m3 as the notch increased to 50 ​%, indicating its crack growth insensitivity. These ionogels can be used as sensors for strain, temperature, and tactile multi-mode sensing, demonstrating a gauge factor of 1.19 and a temperature coefficient of resistance of −3.17/°C-1. Furthermore, these ionogels can be used for the detection of different roughness and as touch screens. The ionogels also exhibit exceptional optical transmittance and environmental stability even at −80 ​°C. Our scalable fabrication process broadens the application potential of these multifunctional ionogels in diverse fields, from smart systems to extreme environments.